Combination of vaginal ultrasonography and Pipelle sampling in the diagnosis of endometrial disease - (:unkn) unknown (Blackwell Publishing, 1996)
In this article, we aimed to investigate the value of Pipelle endometrial sampling with and without sonographic measurement of endometrial thickness in the diagnosis of endometrial disease. We studied prospectively 78 patients scheduled for dilatation and curettage in order to evaluate abnormal uterine bleeding. Sonographic measurement of the endometrial thickness and endometrial sampling with the Pipelle were performed before the curettage. The accuracy of ultrasonography and the Pipelle sampling was measured against the final diagnosis. In 68 cases (87.1%), the endometrial histological results of curettage agreed with those of the Pipelle sampling. Pipelle endometrial sampling had a sensitivity of 73% and a specificity of 100% for endometrial disease. The use of ultrasonography increased the sensitivity of the Pipelle aspiration from 73% to 90%.